Small‐Molecule Proteomimetic Inhibitors of the HIF‐1α–p300 Protein–Protein Interaction. Issue 8 (29th April 2014) - Burslem, George M.; Kyle, Hannah F.; Breeze, Alexander L.; Edwards, Thomas A.; Nelson, Adam; Warriner, Stuart L.; Wilson, Andrew J.
Abstract The therapeutically relevant hypoxia inducible factor HIF‐1α–p300 protein–protein interaction can be orthosterically inhibited with α‐helix mimetics based on an oligoamide scaffold that recapitulates essential features of the C‐terminal helix of the HIF‐1α C‐TAD (C‐terminal transactivation domain). Preliminary SAR studies demonstrated the important role of side‐chain size and hydrophobicity/hydrophilicity in determining potency. These small molecules represent the first biophysically characterised HIF‐1α–p300 PPI inhibitors and the first examples of small‐molecule aromatic oligoamide helix mimetics to be shown to have a selective binding profile. Although the compounds were less potent than HIF‐1α, the result is still remarkable in that the mimetic reproduces only three residues from the 42‐residue HIF‐1α C‐TAD from which it is derived.